2021
DOI: 10.1080/08037051.2021.1904775
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical cardiac disease in women and men with primary aldosteronism

Abstract: Purpose: We tested the sex-specific associations between primary aldosteronism (PA), left ventricular (LV) hypertrophy and LV systolic myocardial function. Material and methods: Conventional and speckle tracking echocardiography was performed in 109 patients with PA and 89 controls with essential hypertension (EH). LV hypertrophy was identified if LV mass index exceeded 47.0 g/m 2.7 in women and 50.0 g/m 2.7 in men. LV systolic myocardial function was assessed by global longitudinal strain (GLS) and midwall sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Exclusive analysis of a prospective study confirmed the association of PA with higher LV internal dimensions and higher LVMI compared with those in subjects with EH (104). Besides, the prevalence of LVH had no significant gender difference in patients with PA (105). What is more, Chen et al demonstrated that patients with PA showed not only LV abnormalities but also impaired right ventricular function because of hyper aldosteronism (106).…”
Section: Aldosterone and Lvhmentioning
confidence: 78%
“…Exclusive analysis of a prospective study confirmed the association of PA with higher LV internal dimensions and higher LVMI compared with those in subjects with EH (104). Besides, the prevalence of LVH had no significant gender difference in patients with PA (105). What is more, Chen et al demonstrated that patients with PA showed not only LV abnormalities but also impaired right ventricular function because of hyper aldosteronism (106).…”
Section: Aldosterone and Lvhmentioning
confidence: 78%
“…Primary aldosteronism was confirmed by recumbent saline infusion testing (SIT), and subtype differentiation was done by cosyntropin-stimulated adrenal vein sampling in all patients, as previously described, and in accordance with current guidelines [3,10]. Interfering antihypertensive medication was withdrawn and replaced by noninterfering medication (primarily doxazosin and/or verapamil) 2-4 weeks prior to diagnostic work up at baseline.…”
Section: Study Populationmentioning
confidence: 99%
“…Conventional and two-dimensional speckle tracking echocardiography were performed following a standardized imaging protocol using a GE Vivid E9 scanner (GE Vingmed Ultrasound, Horten, Norway). Images were postprocessed in the Echocardiography Core laboratory at the University of Bergen, Norway, on workstations equipped with Image Arena Software version 4.2 (TomTec Imaging Systems GmbH, Unterschleißheim, Germany) for conventional measurements and EchoPac software version BT202 (GE Vingmed Ultrasound) for two-dimensional speckle tracking echocardiography as previously reported [10]. Images were analyzed by the same investigator and proofread by a single expert reader following current guidelines for chamber quantification [16].…”
Section: Echocardiographymentioning
confidence: 99%
See 2 more Smart Citations